2015
DOI: 10.1186/s12939-015-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in costs of seeking sexual and reproductive health services in India and Kenya

Abstract: ObjectiveThis study aims to assess inequity in expenditure on sexual and reproductive health (SRH) services in India and Kenya. In addition, this analysis aims to measure the extent to which payments are catastrophic and to explore coping mechanisms used to finance health spending.MethodsData for this study were collected as a part of the situational analysis for the “Diagonal Interventions to Fast Forward Enhanced Reproductive Health” (DIFFER) project, a multi-country project with fieldwork sites in three Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…This measure of equity in expenditure assumes that individuals in the lowest wealth quintile have less capacity to pay and thus if they spend the same or more as those in the highest quintile, this represents a greater proportion of income and constitutes regressive spending 24. Quintile ratios were calculated by comparing mean expenditure in the wealthiest and poorest wealth quintiles and testing for differences using an adjusted Wald-type test of non-linear hypotheses based on the delta method, attributing significance at a 95% confidence level 4 24 25. We define expenditure as weakly pro-rich if there was no significant difference in mean payment between the poorest and wealthiest users and strongly pro-rich if the poorest users paid significantly more than the wealthiest users (quintile ratio <1) 4 24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure of equity in expenditure assumes that individuals in the lowest wealth quintile have less capacity to pay and thus if they spend the same or more as those in the highest quintile, this represents a greater proportion of income and constitutes regressive spending 24. Quintile ratios were calculated by comparing mean expenditure in the wealthiest and poorest wealth quintiles and testing for differences using an adjusted Wald-type test of non-linear hypotheses based on the delta method, attributing significance at a 95% confidence level 4 24 25. We define expenditure as weakly pro-rich if there was no significant difference in mean payment between the poorest and wealthiest users and strongly pro-rich if the poorest users paid significantly more than the wealthiest users (quintile ratio <1) 4 24…”
Section: Methodsmentioning
confidence: 99%
“…In Kenya, unmet need for FP is highest among the poor, with a documented 8–14 percentage point increase in modern contraception use with each increase in household wealth quintile 3. A study in Kenya and India found that poor households spend a significantly higher proportion of their income on reproductive healthcare (including FP), with the poorest households in Kenya spending 10 times the proportion spent by the least poor 4. Many government financial protection policies focus on inpatient events where healthcare expenditure is likely to be catastrophic, yet the greater frequency of outpatient expenses—including for contraceptive services, which affect women in particular—can also push households into poverty5 or reduce care-seeking among the poor 3 6…”
Section: Introductionmentioning
confidence: 99%
“…A study covering Mombasa in Kenya and Mysore in India (2012–13) confirms the highly regressive nature of spending on sexual and reproductive health services. The poorest households spent 2 times as much and 10 times as much as the least poor in India and Kenya, respectively ( Haghparast-Bidgoli et al 2015 ).…”
Section: Overview Of Evidence On Gendered Effects Of Revenue Collectimentioning
confidence: 99%
“…This is an era that the whole world is concerned about the equity issues in relation to health financing. Different income inequality measures are available in the literature such as; Gini coefficient, Atkinson index, generalized-entrophy index, Kakwani index [ 44 46 ]. It is timely that lower-middle-income countries like Sri Lanka encourage more scientific literature on these regards.…”
Section: Discussionmentioning
confidence: 99%